Skeletonema potamos (Bacillariophyta) in Patos Lagoon, southern Brazil: Taxonomy and distribution - Carvalho Torgan, Lezilda (2009)
We analyzed the morphogical features of the centric diatom Skeletonema potamos (Weber) Hasle from Patos Lagoon, southern Brazil, using light and scanning electron microscopy. We discuss the abundance and dis- tribution of the species along the salinity gradient in the lagoon. Samples from the water surface were taken monthly at eight stations along the longitudinal axis of the lagoon, from December 1987 to December 1988. The species were counted by the Utermöhl method, and the density (cells.mL-1) was estimated based on live cells. The morphology of the specimens agrees with the type, from the Little Miami River, Ohio, U.S.A., except for the convexity and the pattern of granules on the valve face. Skeletonema potamos was found in the winter and spring, and was distributed in the limnetic, oligohaline and mesohaline zones of the lagoon. The cell con- centration appeared to be controlled by the salinity, with a significant negative correlation observed. Light and competition probably also influence the development of S. potamos populations in the Patos Lagoon.